BLOOD PRESSURE CONTROL OF NIFEDIPINE GITS 60MG TREATMENT IN PREVIOUSLY UNCONTROLLED HYPERTENSIVE PATIENTS: A PROSPECTIVE, OPEN-LABEL, MULTICENTER, SINGLE-ARM, 8WEEK STUDY. (June 2018) - Liu, L.; Zhang, Y.; Lu, F.; Zhao, Y.; Wu, Y.; Gao, P.; Chen, S.; Chen, L.; Yang, T.; Sun, Y.; Yao, W.; Ji, X.; et al.
Abstract : Objective: Post-marketing surveillance data has confirmed the efficacy and tolerability of 30 and 60 mg Nifedipine GITS in the management of hypertension. However, role of high dose Nifedipine GITS in controlling blood pressure (BP) in patients with uncontrolled BP levels with prior antihypertensive therapy is not studied. This 2nd analysis of ADEPT study aimed to evaluate the effect of Nifedipine GITS 60 mg treatment on 24 hours BP control in uncontrolled hypertensive patients using Ambulatory Blood Pressure Monitoring (ABPM). Design and method: Men and women (18–65 years) whose BP was uncontrolled with prior antihypertensive monotherapy were included in a prospective, open-label, multicenter, single-arm study. Patients received oral Nifedipine GITS 60 mg for 8 weeks, OD. BP data was obtained at baseline, week 2, 4, and 8. Mean 24-h systolic (SBP) and diastolic blood pressure (DBP) data was obtained through 24-h ABPM at baseline and after Week 8. BP reduction at each hour and throughout 8-week study period was analyzed along with heart rate (HR). Results: Patients who started both baseline and week 8 ABPM between 8:00 and 11:59AM were included in the analyses (n = 138, age = 55.6 ± 8.1 years, 58% men, 42% women). Hourly variation in SBP and DBP at baseline and week 8 is represented in Fig.1. Mean 24-h SBP decreased from 129.1 ± 16.1 mmHg to 121.6 ± 12.7 mmHg and DBP decreased from 79.1 ± 10.1 mmHg to 76.0 ± 9.2 mmHg. T/P ratio for SBP was 0.71 and 0.63 for DBP. Mean change in SBP and DBP for last 4-h at baseline and week 8 was 133.4 ± 15.0 mmHg and 126.3 ± 12.6 mmHg, 82.9 ± 9.1 mmHg and 80.0 ± 8.8 mmHg respectively. Mean change in SBP and DBP for last 6-h at baseline and week 8 was 131.9 ± 14.9 mmHg and 124.6 ± 11.9 mmHg, 81.6 ± 9.0 mmHg and 78.4 ± 8.8 mmHg respectively. 24-h variation in HR was 1.5 bpm. Figure. No caption available. Conclusions: Nifedipine GITS showed good efficacy in the last dosing time along with good BP control for 24-h in patients with uncontrolled BP with prior antihypertensive monotherapy.